2004
DOI: 10.1080/10284150410001704525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil on the Central Nervous System: A New Potential Antidepressant?

Abstract: In the last 100 years major depression has increased worldwide. In this study we provided coconut fat (CF, rich in saturated fatty acids) or fish oil (FO, rich in n-3 polyunsaturated fatty acids) to female rats throughout pregnancy and lactation and then to their offspring post-weaning and examined lipid brain profile and the possible effect of FO as antidepressant agent in the offspring in adulthood (F1). Rats were submitted to forced swimming test, elevated plus maze, Morris water maze and open field. Peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 57 publications
(58 reference statements)
2
38
0
1
Order By: Relevance
“…One or a combination of these factors could contribute to increased depression and aggression scores reported in response to n-3 PUFA deprivation in rats. 15,39,[59][60][61][62] As CREB has been implicated in the pathophysiology of depression as well as of bipolar disorder, 33,63,64 n-3 PUFAs' ability to regulate CREB could be related to their effects in these diseases. CREB requires phosphorylation in order to transcribe CREB-regulated genes, including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…One or a combination of these factors could contribute to increased depression and aggression scores reported in response to n-3 PUFA deprivation in rats. 15,39,[59][60][61][62] As CREB has been implicated in the pathophysiology of depression as well as of bipolar disorder, 33,63,64 n-3 PUFAs' ability to regulate CREB could be related to their effects in these diseases. CREB requires phosphorylation in order to transcribe CREB-regulated genes, including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to condition limitation, we could not measure the AA concentration in the shell after EPA treatment. However, several studies have demonstrated that EPA treatment can decrease AA concentration or n-6/n-3 ratio in different regions of the brain (Naliwaiko et al, 2004;Amusquivar et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial health effects of ω-3 PUFAs are well defined: they are essential for the normal growth and development of the brain and nervous system and are also thought to exert beneficial effects during the treatment of coronary artery disease, hypertension, arthritis, clinical depression, anxiety, inflammatory and autoimmune disorders and cancer (Cao and Hur, 2005;Correa et al, 2008;Jeong et al, 2006;Lee et al, 2006;Su et al, 2003;Naliwaiko et al, 2004;Green et al 2006;Yehuda et al, 2005;Nemets et al, 2002).…”
Section: Introductionmentioning
confidence: 99%